A Cartesian Scheme for Compressible Multimaterial Hyperelastic Models with Plasticity (Communications in Computational Physics, 2017)
We describe a numerical model to simulate the non-linear elasto-plastic dynamicsof compressible materials. The model is fully Eulerian and it is discretized ona fixed Cartesian mesh. The hyperelastic constitutive law considered is neohookeanand the plasticity model is based on a multiplicative decomposition of the inverse deformationtensor. The model is thermodynamically consistent and it is shown to bestable in the sense that the norm of the deviatoric stress tensor beyond yield is nonincreasing. The multimaterial integration scheme is based on a simple numerical fluxfunction that keeps the interfaces sharp. Numerical illustrations in one to three spacedimensions of high-speed multimaterial impacts in air are presented.